3D Printing of Next‐generation Electrochemical Energy Storage Devices: from Multiscale to Multimaterial. Issue 2 (28th June 2021) - Xu, Xi; Tan, Yong Hao; Ding, Jun; Guan, Cao
Abstract : The increasing energy requirements to power the modern world has driven active research into more advanced electrochemical energy storage devices (EESD) with both high energy densities and power densities. Wide range of newly discovered materials with promising electrochemical properties has shown great potential for next‐generation devices, but their performance is normally associated with contradicting demands of thin electrodes and high mass loading that can be hardly achieved for practical applications. Design of three‐dimensional (3D) porous electrodes can increase the mass loading while maintaining the effective charge transport even with thick electrodes, which has proven to be efficient to overcome the limitations. 3D structures have also been demonstrated excellent structural stability to withstand strong strains and stresses generated during charge/discharge cycle. 3D printing, which can fabricate various delicate and complex structural designs, thus offering brand‐new opportunities for the rational design and facile construction of next‐generation EESDs. The recent developments in 3D printing of next‐generation EESDs with high performance are reviewed. Advanced/multiscale electrode structures, such as hierarchically porous structure that can be constructed via high‐resolution 3D printing or with post‐treatment, are further emphasized. The ability of current 3D printing techniques to fulfill multimaterial printing to fulfill simple packaging will be covered. Abstract : The increasing energy requirements to power the modern world has driven active research into more advanced energy storage devices (EESDs) fabrication, where can be fulfilled by multiscale and multilateral 3D printing.